First report of Phytophthora sojae causing root rot in soybean [Glycine max (L.) Merr.] in Alberta, Canada. (January 2017) - Chang, K.F.; Hwang, S.F.; Ahmed, H.U.; Zhou, Q.; Strelkov, S.E.; Conner, R.L.; McLaren, D.L.; Henriquez, M.A.; Harding, M.W.; Turnbull, G.D.
Abstract: Soybean [ Glycine max (L.) Merr.] has great potential as an alternative crop in western Canada. Root rot is a common constraint in soybean production, and the occurrence of root rot was documented in all 29 fields surveyed in southern Alberta in 2014. Phytophthora spp. cause seed rot, pre- and post-emergence damping-off, and stem and root rot wherever soybean is produced, but it has not been previously reported in association with soybean in Alberta. Following a survey of soybean fields in 2014, root tissue with typical symptoms of root rot was plated onto a selective growth medium, and two isolates were designated as putative Phytophthora spp. based on their colony characteristics. These two isolates were homothallic on lima bean agar, producing smooth, thick-walled oospores and mostly paragynous with some amphigynous antheridia. Based on these criteria, the two isolates were identified as Phytophthora sojae Kaufmann & Gerdemann. Sequencing of the internal transcribed spacer (ITS) region revealed 100% identity with ITS sequences of P. sojae available in GenBank. A pathogenicity test revealed that both isolates of P. sojae were able to cause root rot on soybean and produce typical chocolate brown stem lesions just above the base of the plants. The two isolates were classified as races 4 and 28 of P. sojae based on their virulence on a set of soybean differential cultivars. Race 28 was more virulent than race 4 on the soybean cultivars 'XBP27005' and 'XBP29002'. Regression analysis showed the positive linear relationships of the log of inoculum density with disease severity, and negative linear relationships with seedling emergence, plant height, and plant biomass. This is the first report of Phytophthora spp. causing root rot in soybean in Alberta. Highlights: Two isolates from a 2014 soybean survey were identified as Phytophthora sojae. Identity basis: fungal physical characteristics and ITS sequences. The isolates were classified as races 4 and 28, based on soybean cultivar reaction. Higher isolate density increased disease severity, reduced emergence and growth.